Advanced Microgrid Protection Utilizing Zero Sequence Components With Hard-Ware-in-the-Loop Testing - Zahra Ghanem; Feras Alasali; Naser El-Naily; Hassen Loukil; Haytham Y. Mustafa; Saad M. Saad; Abdelaziz Salah Saidi; William Holderbaum (IEEE Access)
Microgrid protection and ground fault management are critical aspects of modern power distribution systems, especially with the increasing integration of Distributed Generators (DGs) such as renewable energy sources. Effective protection schemes are essential to ensure the reliability, safety, and resilience of microgrids under various fault conditions. This study addresses a new advancement in microgrid protection and ground fault management. Firstly, the research integrates zero sequence components into the time-inverse characteristics of phase Overcurrent Relays (OCR) and creates a dynamic scheme between two group settings for phase and ground faults. This enhancement improves ground fault detection and provides robust backup for ground OCR, thereby enhancing the overall reliability of microgrid protection schemes. Secondly, the study demonstrates the use of Configurable Function Blocks (CFCs) in digital relays to dynamically adjust relay settings based on zero sequence current detection. This functionality optimizes relay performance under varying fault conditions, addressing mis-coordination issues in low-value ground fault scenarios at traditional OCR scheme and improving fault detection and clearance times. The proposed strategy is extensively validated through Hardware-in-the-Loop (HIL) testing, ensuring its feasibility and effectiveness in real-world scenarios. HIL testing confirms the practical applicability and robustness of the proposed protection scheme, enhancing its reliability. Finally, the study provides a comprehensive framework for the implementation of the proposed protection strategy in real-case protective relays. It includes a detailed methodology and validation process, offering practical guidance for operators to implement and optimize microgrid protection systems.